Indonesian Obstacles in the Implementation of Assets Confidential Proceedings from Corruption Crimes Overseas Based on the UN Convention AS Set Forth in UNCAC - Muhammad Anwar; Agus Surono (Dinasti Research, 2025)
The eradication of corruption in Indonesia, classified as an extraordinary crime, has not been optimally implemented, particularly in addressing perpetrators who flee to other countries. The international community, through the United Nations Convention against Corruption (UNCAC), has committed to combating corruption among member states. Corruption, in addition to being an extraordinary crime at the national level, has also become an international (transnational crime) threat, endangering global society and the international economy. Indonesia’s commitment to eradicating corruption includes efforts to recover and repatriate assets resulting from corruption that have been moved abroad. This has been carried out through cooperation agreements, including extradition treaties and mutual legal assistance agreements, with countries where corrupt individuals hide stolen assets. While these measures have shown progress, they remain suboptimal due to obstacles in implementation, arising from political and legal factors as well as the execution of agreements. Consequently, convicted perpetrators of corruption in Indonesian courts are often able to resist enforcement due to differences in legal systems between Indonesia and partner countries. To optimize efforts and reduce these legal and implementation challenges, strong political will from the Indonesian government and proactive diplomatic relations between heads of state and law enforcement officials are needed to foster effective cooperation in pursuing corrupt individuals hiding abroad.